Modeling Keynesian Consumption Function for Community Financial Education - Michael Elonge (Adult Education Research Conference, 2022)
Modeling Keynesian Consumption Function for Community Financial Education demonstrates a basic teaching to caseworkers to develop their financial education skills to become better financial mentors to the communities they serve.
Keywords: caseworkers; community; consumption-function; financial education; welfare